Geophysical parameters estimation with TerraSAR-X of outlet glaciers in the Transantarctic Mountains - Floricioiu, Dana; Jezek, Kenneth; Bäßler, Michael; Abdel Jaber, Wael (2012 IEEE International Geoscience and Remote Sensing Symposium, 2012)
We discuss TerraSAR-X observations of three Transantarctic Mountain (TAM) outlet glaciers: Byrd, Nimrod and Beardmore. High resolution TerraSAR-X data acquired over the area in late 2009 and late 2010 using left looking mode were processed to generate detailed 2D ice velocity maps by means of speckle tracking. The ice dynamics from East Antarctica to Ross Ice Shelf through the three TAM fjords is compared. The position of the grounding line is determined by DInSAR and compared to other sources. The surface velocity at the grounding line is needed for estimating the magnitude of ice flux from East Antarctica fast glaciers into the Ross Ice Shelf.